2020
DOI: 10.3354/esr01034
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence for allopatric speciation of the Siberian ibex Capra sibirica in India

Abstract: Montane systems, formed by a series of climatic oscillations and temporal topographic metamorphoses, have broken up the contiguous distribution of widespread species and accelerated allopatric speciation. We used a partial fragment of the mitochondrial cytochrome b (cytb) gene to address speciation across the entire range of the Siberian ibex Capra sibirica. We demonstrated that the Siberian ibex is a polytypic species, plausibly formed by a combination of at least 2 species and/or 3 to 4 sub-species. Bayesian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
1
14
0
1
Order By: Relevance
“…Consequently, the ever-increasing temperature in the eco-sensitive habitats of the trans-Himalayas due to global warming may alter the habitat suitability and physiological responses of the ibex. The Himalayan ibex forms the peripheral population of the widely distributed Siberian ibex and Joshi et al [ 19 ] also reported that it is an evolutionary distinct phylogenetic lineage of the Siberian ibex. Thus, we propose this unit or phylogenetically distinct lineage to be managed at a regional level.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Consequently, the ever-increasing temperature in the eco-sensitive habitats of the trans-Himalayas due to global warming may alter the habitat suitability and physiological responses of the ibex. The Himalayan ibex forms the peripheral population of the widely distributed Siberian ibex and Joshi et al [ 19 ] also reported that it is an evolutionary distinct phylogenetic lineage of the Siberian ibex. Thus, we propose this unit or phylogenetically distinct lineage to be managed at a regional level.…”
Section: Discussionmentioning
confidence: 99%
“…In India, the Himalayan ibex is distributed in Ladakh and Himachal Pradesh. The study was carried out in the following areas—Ladakh (LA): Leh district (Changthang, Nubra and Sham) and Kargil district (Drass and Zanskar) while in Himachal Pradesh it was carried out in the Lahaul and Spiti district (LS) [ 19 , 20 ], falling under the trans-Himalayan region extending from 31–33° N latitudes to 75–80° E longitudes ( Figure 1 ). The study area covers a total of 106,014 km 2 (86,983 km 2 of Ladakh and 19,031 km 2 of Lahaul-Spiti) with varying elevation from 2400 to 6000 m, exposed to extreme harsh climatic conditions with cold temperature, little rainfall and reduced oxygen levels with high levels of UV radiation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations